PENGARUH EXPERTISE KOMITE AUDIT DAN FRAUDULENT FINANCIAL STATEMENT TERHADAP AUDIT REPORT TIMELINESS DENGAN DIVERSITAS GENDER SEBAGAI VARIABEL MODERASI - Shinta Fitriani; Dian Saputra (Bilancia : Jurnal Ilmiah Akuntansi, 2026)
This study aims to examine the influence of audit committee expertise and fraudulent financial statements on audit report timeliness, with gender diversity acting as a moderator, in property and real estate companies listed on the Indonesia Stock Exchange for the period 2023–2024. This study employs a quantitative approach using purposive sampling, resulting in 142 observations. Data analysis was conducted using multiple linear regression with a Moderated Regression Analysis (MRA) approach. The results indicate that audit committee expertise has a positive and significant effect on audit report timeliness, whilst fraudulent financial statements do not show a significant effect. Furthermore, gender diversity was found to weaken the effect of audit committee expertise on audit report timeliness, but did not play a role in moderating the relationship between fraudulent financial statements and audit report timeliness. These findings indicate that audit committee expertise is a key factor in improving the timeliness of audit reporting, whilst the effectiveness of gender diversity depends on the context of the relationships between the variables tested.